Creating the Relationship between School and Community of Ban Bo School under the Jurisdiction of Sisaket Primary Educational Service Area Office 3 - Chansamoot, Warayut Chansamoot1; Wongwatkasem , Wiralphat (Journal for Developing the Social and Community, 2022)
The research purposes were: (1) to search level of the creating the relationship between school and community of Ban Bo School under the jurisdiction of Sisaket Primary Educational Service Area Office 3; and (2) to compare the student parents opinion on the creating the relationship between school and community of Ban Bo School under the jurisdiction of Sisaket Primary Educational Service Area Office 3, classified by education level. This research was the quantitative research. The population was the 100 student parents of Ban Bo School under the jurisdiction of Sisaket Primary Educational Service Area Office 3, academic year 2020. The sample group consisted of 80 student parents, determined by the Krejcie & Morgan table, and selected by the simple random sampling method. The research instrument was the questionnaire. The data analysis statistics were the frequency, percentage, mean, standard deviation, t-test, and one-way analysis of variance. The research findings were: (1) the creating level of the relationship between school and community found the overall was at high level. The each aspect consideration found the highest mean was the community service aspect, followed by the assistance and supporting from community aspect, and the lowest mean was the organizing groups, clubs, associations, or foundations aspect; and (2) the comparison of school parents on the creating relationship between school and community found the school parents with different education level had the opinion on the creating relationship between school and community of Ban Bo School under the jurisdiction of Sisaket Primary Educational Service Area Office 3 were different with statistics significance level .05